Multi-level factors affecting timely electronic documentation of medication administration: a hierarchical linear modeling approach. Issue 2 (1st July 2017) - Raman, Roopa; Green, Kimberly
Abstract: This study applies a systematic hierarchical linear modeling approach to identify factors impacting timely documentation of medication administration on electronic medication administration record (eMAR) systems. Delayed documentation of medications poses significant risks to patient safety. Multi-level quantitative data were collected from a large urban hospital system, spanning the non-physician clinician workforce across 27 patient-care units. Data suggests the overall perception of psychological safety on one's unit was a significant predictor of individual clinicians' timely eMAR documentation. The impact of each clinician's personal psychological safety was nuanced by his/her patient-care unit and type of hospital. Other characteristics of the provider's patient-care unit were also relevant. Thus, even though timely eMAR documentation is an individual-level activity, it is predicted by characteristics beyond complete control of the individual. We illustrate the value of applying systematic hierarchical linear modeling approach to better illuminate the problem of consistently achieving timely eMAR documentation across all providers.